Original paperThe effect of superficial femoral artery stenting and some atherosclerosis risk factors on changes in selected global endothelial function tests in patients with chronic lower limb ischemia. A pilot study - Budzyński, Jacek; Wiśniewska, Joanna; Wasielewski, Marcin; Suppan, Karol (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Introduction: Endothelial dysfunction is the main pathomechanism of atherosclerotic processes and their complications. Revascularization and control of atherosclerosis risk factors may improve the global endothelial function. Aim: Assessment of the relationships between the level of selected atherosclerosis risk factors and changes in noninvasive endothelial function parameters during one year long follow-up after superficial femoral artery (SFA) stenting. Material and methods: Seventeen male patients after SFA stenting were studied. Before the endovascular procedure, one day after it, and after 1, 3, 6, and 12 months after SFA stenting the values of global endothelial function parameters were evaluated, as follows: ankle-brachial index (ABI), flow-mediated brachial artery dilatation, distensibility coefficient, and Doppler parameters of blood flow in brachial and common carotid arteries in response to brachial ischemia and nitroglycerin sublingual application as well as intima-media complex thickness. Results: Of the studied parameters only ABI improved significantly after SFA stenting. The changes in values of investigated endothelial function parameters were related to presence of atherosclerotic risk factors, such as age above 62 years, hypercholesterolemia, diabetes, and hypertension. Generally, global endothelial function tests were worse in patients with these conditions before the endovascular procedure, then they improved to reach the level observed in individuals without cardiovascular risk factors already after 3 to 6 months after SFA stenting. Conclusions: The SFA stenting together with adequate pharmacotherapy may reduce the negative effect of comorbidities on the global endothelial function and vasodilatation reserve of brachial and carotid arteries.